An environmental pollutant to an efficient solar vapor generator: an eco-friendly method for freshwater production. Issue 12 (27th May 2021) - Wani, Tawseef Ahmad; Garg, Parul; Bera, Ashok
Abstract : The solar-driven water evaporation technique has shown enormous potential for freshwater generation. Solar vapor generator made of carbonized coconut husk shows an evaporation rate of 3.6 kg m −2 h −1 with the ability to purify seawater and sewage. Abstract : The solar-driven water evaporation technique to produce clean water has shown enormous potential as an energy-efficient solution for global freshwater scarcity. Designing a cost-effective and efficient solar vapor generator (SVG) using an underutilized natural source that causes environmental pollution will be an eco-friendly method for freshwater generation. We developed an SVG by simply carbonizing the surface of a piece of coconut husk using a household liquefied petroleum gas stove. The naturally porous structure of coconut husk enhances light absorption, and the 3D assembly promotes heat energy harvesting from the environment, leading to an effective energy input of 1.6 kW m −2 under 1 sun illumination (1.0 kW m −2 ). Our carbonized coconut husk evaporator shows an evaporation rate of 3.6 kg m −2 h −1 . Due to simple design techniques, negligible material cost, and large-scale availability combined with the already existing coconut coir industries, carbonized coconut husk-based SVGs can provide an affordable method for freshwater generation.